E-Filing System Determinant of VAT Revenue Collection in Tanzania: A case of Large Tax Payers. - NGUVAVA , Heriel Emanuel; ANATORY , Levina (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2025)
This study examined Electronic Tax Filing (E-filing) system as a determining factor of Value Added Tax (VAT) revenue collection in Tanzania, with a focus on large taxpayers. The specific objectives were, to examine the relationship between e-filing and VAT revenue collection and to assess the causality between e-filing and VAT revenue collection. This study was guided by the Technological Acceptance Model (TAM), which emphasizes on accessibility, rate of usage and perceived usefulness of technology. A quantitative descriptive design was employed, utilizing both primary and secondary data. Time series data covering the period 2015 to 2024 were sourced from the Tanzania Revenue Authority (TRA), while primary data were collected using structured questionnaires distributed to selected TRA officials and large taxpayers purposively. Statistical methods for data analysis used include descriptive statistics, Pearson correlation analysis and linear regression. Findings revealed a strong positive correlation (r = 0.792 and r =0.821) between system accessibility, e-filing, and VAT revenue collection in Tanzania. Results further revealed system accessibility significantly and positively influence VAT revenue collection where positive improvement in accessibility by 1unit lead to 45.8 units’ increment in VAT revenue collection. These results imply that e-filing significantly contributes to VAT collection by enhancing efficiency (save cost of filing), reducing errors, and promoting timely compliance. This study recommends to the government of Tanzania to continuously invest in e-filing infrastructure, enforcement strategies, and digital literacy programs to maximize the benefits of digital tax administration.